2014
DOI: 10.1002/app.40574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fracture behaviors of multilayered propylene–ethylene copolymer/polypropylene homopolymer composites with the essential work of fracture

Abstract: As one of the most appropriate techniques for evaluating the fracture behavior, the essential work of fracture (EWF) was introduced to investigate the fracture toughness of multilayered composites. Propylene–ethylene copolymer (CPP)/polypropylene homopolymer (HPP) alternating multilayered composites with 2–128 layers were prepared though multilayered coextrusion. Polarized optical microscopy photographs revealed that the CPP and HPP layers aligned alternately vertical to the interfaces and continuously paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…And obviously the individual phase continuity along the extrusion direction became lower. In addition, through the measuring the thicknesses of the CPP and HPP layers in the POM micrographs, a method which was described detailed in our previous studies, the volume fractions of the POE in the multilayered structure were found to have the same value of ∼12%. As all of the multilayered sheets were prepared with the same processing conditions, including the same temperature and extruder speed, the proportions of two components did not change much with the number of layers.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…And obviously the individual phase continuity along the extrusion direction became lower. In addition, through the measuring the thicknesses of the CPP and HPP layers in the POM micrographs, a method which was described detailed in our previous studies, the volume fractions of the POE in the multilayered structure were found to have the same value of ∼12%. As all of the multilayered sheets were prepared with the same processing conditions, including the same temperature and extruder speed, the proportions of two components did not change much with the number of layers.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, through the interaction between the crazing and shear‐banding those were formed at the interface, the multilayered polycarbonate (PC) and styrene‐acrylonitrile copolymer (SAN) materials could present ductile tensile fracture behavior . And our previous studies showed that the fracture toughness of multilayered propylene–ethylene copolymer (CPP)/polypropylene homopolymer (HPP) was higher than that of conventional blends with the same components by essential work of fracture (EWF) . However, the tear behavior and the associated fracture mechanism of multilayered blends have received less attention due to the difficulty to obtain the alternating layered samples.…”
Section: Introductionmentioning
confidence: 99%
“…– and responsible for many of their interesting properties. It is thought to be able to provide many useful properties for different materials, such as excellent mechanical properties, dielectric properties, barrier properties, flame‐resistant materials, electromagnetic shielding materials and so on . Thus, much attention has been paid to the preparation of materials with a multilayered structure.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, as one of the key properties for multilayered structures, the mechanical performance of polymeric materials with such a structure has been subjected to a considerable amount of attention . The multilayered structure fabricated by HSTWIM is thought to be able to provide interesting mechanical behavior for the overall materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation